Implementasi Program Pemagangan Dalam Negeri sebagai Upaya Meningkatkan Kompetensi Tenaga Kerja di Provinsi Kalimantan Utara - Nazli Silviani; Muhammad Hairul Saleh; Letizya Dyastari (Jurnal Ilmu Pemerintahan, 2023)
This study aims to determine how the implementation of the Domestic Apprenticeship Programme is carried out in accordance with the indicators of successful policy implementation according to George Edward (III). The research was conducted in North Kalimantan Province using descriptive qualitative methods and data collection techniques were carried out by means of observation, interview and documentation research, provided by the North Kalimantan Provincial Manpower Office. The sources of this research were the Head of the Training and Placement Division, the Head of the Training and Productivity Section of the Manpower and Transmigration Office, the HRD of PT. IDEC AWI and HRD of PT. Tarakan Elektrik Brother, 8 apprenticeship participants in 2018-2021. The results showed that the implementation of the Domestic Apprenticeship Programme in North Kalimantan Province has generally gone well. With four indicators of successful implementation that are well implemented and optimal which can be seen through communication between the government and the Apprenticeship Network Communication Forum (ANCF) companies, human resources, budgets and facilities, the attitude of the Government that is committed to implementing the Apprenticeship Programme and Standard Operating Procedures (SOP) that are carried out according to the mechanism of implementing the Domestic Apprenticeship Programme. Suggestions from the author that the Government is expected to direct participants to take the professional certificate competency test from the National Professional Certificate Agency (NPCA) after participants take part in the Domestic Apprenticeship Programme in North Kalimantan Province.